The Influence of Hexagon Fraud Theory on Fraudulent Financial Reporting: The Moderating Role of the Audit Committee - Putra, Mukhlas Adi; Achmad, Tarmizi (Journal of Ecohumanism, 2024)
The purpose of this study is to review the potential for fraud with the fraud hexagon theory. In addition, statistical analysis is conducted to determine the moderating impact of the audit committee. Uses the Moderated Regression Analysis (MRA) technique and F-Score as a measurement of FFR. The sample consisted of 492 observations from 2020 to 2023 consumer cyclical sector companies. This study indicates that external pressure, ineffective monitoring, quality of external audit, ceo duality, political connection, and arrogance have a significant effect. Meanwhile, the financial targets, auditor switching, change in director, and nature of the industry do not have a significant effect. Audit committees can reduce the impact of financial targets, ineffective monitoring, changes in directors, ceo-duality, political connections, and arrogance. However, it is not possible to control for the impact of external pressure, auditor switching, quality of external audit, and nature of the industry. The audit committee can reduce negative impacts within the company, while external impacts have not been able to reduce them. Thus, management must pay more attention to the existence of the audit committee as a front guard to prevent fraud.